Overhead Grants’ Usage and Educational Institutions in Nigeria: Data Envelopment Analysis Perspective - Ololade, Babatunde Moses; Odewole, Philip Olawale; Akande, Adesola Adebayo (Archives of Business Research, 2022)
This study appraised the utilization of overhead grants’ efficiency among federal educational institutions in Nigeria between2011-2019. Data for the study were sourced from the Annual Audited Financial Statements of the public sector entities. The sampled size for the study comprised (25) federal educational institutions out of 69 federal educational institutions drawn across the country among four (4) geo-political zones. Data were analyzed using Data Envelopment Analysis. The results of the average efficiency scores from both CCR and BBC models showed that the entities were averagely efficient in overhead grants’ utilization. Overall results showed that federal educational institutions have high capacity to absorb sufficient overhead grants from the center. The study therefore concluded that there is need for an improved overhead grants releases to the federal educational institutions to achieve effective service deliveries of their core mandates. The study recommended a continuous assessment and periodic appraisal of the overhead grants’ utilization among the institutions by their supervising ministry to achieve full efficiency.